Tracking of unfamiliar odors is facilitated by signal amplification through anoctamin 2 chloride channels in mouse olfactory receptor neurons - Neureither, Franziska; Frings, Stephan; Möhrlen, Frank (Physiological reports, 2017)
Many animals follow odor trails to find food, nesting sites, or mates, and they require only faint olfactory cues to do so. The performance of a tracking dog, for instance, poses the question on how the animal is able to distinguish a target odor from the complex chemical background around the trail. Current concepts of odor perception suggest that animals memorize each odor as an olfactory object, a percept that enables fast recognition of the odor and the interpretation of its valence. An open question still is how this learning process operates efficiently at the low odor concentrations that typically prevail when animals inspect an odor trail. To understand olfactory processing under these conditions, we studied the role of an amplification mechanism that boosts signal transduction at low stimulus intensities, a process mediated by calcium‐gated anoctamin 2 chloride channels. Genetically altered Ano2−/− mice, which lack these channels, display an impaired cue‐tracking behavior at low odor concentrations when challenged with an unfamiliar, but not with a familiar, odor. Moreover, recordings from the olfactory epithelium revealed that odor coding lacks sensitivity and temporal resolution in anoctamin 2‐deficient mice. Our results demonstrate that the detection of an unfamiliar, weak odor, as well as its memorization as an olfactory object, require signal amplification in olfactory receptor neurons. This process may contribute to the phenomenal tracking abilities of animals that follow odor trails.